Application of the Simplified Water Quality Index (ISQA) in water quality assessment in the Ocloro River, San José, Costa Rica - Chaves-Chaves, Elena (2024)
Water has an essential role in the development of life. Therefore, it is associated to the economic and social progress of communities. Hence, it is necessary to have water quality. Water analysis is required to understand its physical, chemical, and biological conditions according to the final use. This article presents the findings of the water quality assessment using the Simplified Water Quality Index (ISQA) on the Ocloro River located in the San José. The indicators that ISQA apply are temperature, dissolved oxygen (OD), electrical conductivity (CE), chemical oxygen demand (DQO), and total dissolve solids (SST). The indicators were measured in five points along the river. As a result, the Ocloro river manifests a significantly high pollution and environmental degradation level. These observations have significant repercussions on the development and quality of life for communities near its area of influence.